Monetary Momentum - Andreas Neuhierl; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2017)
We document a large return drift around monetary policy announcements by the Federal Open Market Committee. Stock returns start drifting up 25 days before expansionary monetary policy surprises, whereas they decrease before contractionary surprises. The cumulative return difference across expansionary and contractionary policy decisions amounts to 2.5% until the day of the policy move and continues to increase to more than 4.5% 15 days after the meeting. The return drift is a market-wide phenomenon, holds for all industries, and many international equity markets. In the cross section of stocks, size, value, profitability, and investment do not exhibit differential return drifts. Momentum is an exception, because past losers plummet around contractionary monetary policy surprises. A simple trading strategy exploiting the drift around FOMC meetings increases Sharpe ratios relative to a buy-and-hold investment by a factor of 4.
Keywords: E31; E43; E44; E52; E58; G12; 330; return drift; policy speeches; expected returns; macro news